2021
DOI: 10.5296/jpag.v11i4.19241
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Benefits of a One-Stop Medical and Financial Support Program: From the Standpoint of Patients of Eduardo L. Joson Memorial Hospital in the Philippines

Abstract: This study described the benefits of the Malasakit Center based on the perspectives and experiences of patients of Eduardo L. Joson Memorial Hospital. It employed mixed research methods and interviews as the primary data collection tool. The study was conducted in March 2020 with thirty patients and patient's relatives receiving services of the hospital. Most of the respondents are male and within the age bracket of 30 to 39 years old. All the participants reflected a positive response to Malasakit Center, as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…The ratings can be attributed to the convenience that the different agencies by which they needed to approach for assistance are found in one setting. This was explained by Santiago et al (2021) stating that the program seeks to improve convenience.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ratings can be attributed to the convenience that the different agencies by which they needed to approach for assistance are found in one setting. This was explained by Santiago et al (2021) stating that the program seeks to improve convenience.…”
Section: Resultsmentioning
confidence: 99%
“…The Law carries out the government's pledge to institutionalize the creation of a onestop shop where patients can access the medical and other financial aid offered by various authorities which can be done through a program or system mechanism like streamlining the business process. The study by Santiago et al (2021) revealed positive feedback on the services of the Malasakit Center. The Center's improved service accessibility was highlighted by the outcome.…”
Section: Measures To Continuously Improve the Level Of Satisfaction O...mentioning
confidence: 96%